Efficacy and safety of a comprehensive educational antimicrobial stewardship program focused on antifungal use. Issue 3 (March 2020) - Martín-Gutiérrez, Guillermo; Peñalva, Germán; Ruiz-Pérez de Pipaón, Maite; Aguilar, Manuela; Gil-Navarro, María Victoria; Pérez-Blanco, José Luis; Pérez-Moreno, María Antonia; Amaya-Villar, Rosario; Ferrándiz-Millón, Carmen; Gascón, María L.; Goycochea-Valdivia, Walter A.; Jiménez-Mejías, Manuel E.; et al.
Highlights: The PRIOAM improved antifungal use in patients with hospital-acquired candidemia. It resulted in a proportional reduction of antifungal consumption of 38.4%. The most frequently prescribed antifungal agent was fluconazole. The number of Candida spp. with antifungal resistance was remarkably low (4.7%). The reduction in antifungal consumption was safe. Summary: Objective: Few data exist regarding the impact of antimicrobial stewardship programs on antifungal use. We evaluated the efficacy and safety of a comprehensive long-term antimicrobial stewardship program (ASP) focused on antifungal use. Methods: During a 9-year period, we quarterly assessed antifungal consumption, incidence density of hospital-acquired candidemia, Candida spp. distribution, antifungal resistance, and crude death rate per 1000 occupied bed days (OBDs) of hospital-acquired candidemia. We performed segmented regression analysis of interrupted time series. Results: A significant change in trend was observed for antifungal consumption, with a sustained reduction of -0.87% per quarter (95% confidence interval [CI], −1.36 −0.38, p < 0.001), accounting for a final reduction of −38.4%. The main reduction was produced in fluconazole, with a sustained reduction of −1.37% per quarter (95%CI, −1.96 −0.68, p <0.001). The incidence density of hospital-acquired candidemia decreased, with a change in slope of −5.06% cases per 1000 OBDs per year (95%CI, −8.23 −1.77, p = 0.009). The 14-day crude death rate per 1000 OBDs dropped from 0.044 to 0.017 (−6.36% deaths per 1000 OBDs per year; 95%CI, −13.45 −1.31, p = 0.09). Conclusions: This ASP has succeeded in optimizing the use of antifungal with a long-lasting reduction without increasing the incidence, neither the mortality, of hospital-acquired candidemia.